Pelatihan Microsoft Word dan Microsoft Excel pada Siswa SMK Negeri 1 Tinambung - Nahya Nur; Sulfayanti Sulfayanti; Arnita Irianti (Madani : Indonesian Journal of Civil Society, 2022)
The development of technology has changed the writing and data storage media from physical to digital form. This is also supported by the development of the world of engineering software which is now able to create and facilitate various human needs through computer applications. The Informatics Study Program, Faculty of Engineering, University of West Sulawesi, through a community service program, carried out computer application training activities to operate the two applications. This service activity aims to add insight and knowledge to the community, especially Vocational High School students on the use of computer applications, especially Microsoft Word and Microsoft Excel. The activities carried out can be said to be successful based on the achievements of the activities evaluated by looking at the abilities of the participants. As a result, this activity was able to help participants gain additional knowledge about Microsoft Word and Microsoft Excel applications, as well as provide opportunities for students to gain experience being involved in training activities according to their field of knowledge.